FRI0215 Comparative efficacy and retention rate of tocilizumab and tnf inhibitors used in combination with methotrexate as first-line biologic therapy in rheumatoid arthritis: data from a multicentre observational registry. (15th June 2017) - Favalli, EG; Biggioggero, M; Puttini, P Sarzi; Atzeni, F; Fusaro, E; Grosso, V; Pellerito, R; Gorla, R; Bazzani, C; Marchesoni, A; Caporali, R
Abstract : Background: Despite a demonstrated superiority of interleukin-6 over tumour necrosis factor (TNF) blockade when used as monotherapy, the choice of the first biologic agent (bDMARD) for treating rheumatoid arthritis (RA) in combination with methotrexate (MTX) is still a challenge for rheumatologist. Objectives: To retrospectively evaluate in a multicentre observational cohort of Northern Italy (the LORHEN registry) the 6- and 12-month comparative drug survival and remission rate of tocilizumab (TCZ) and TNF inhibitors (TNFis) used as first bDMARD in combination with MTX. Methods: All RA patients treated with TCZ or a TNFi as first-line bDMARD with at least 12-month follow-up were selected from the LORHEN registry. The analysis was limited to the period from January 2009 to May 2016 and to patients receiving either TCZ or TNFi in combination with MTX, excluding bDMARD monotherapy. Six- and 12-month clinical remission rate was defined as achievement of disease activity score 28 calculated by using erythrosedimentation rate (DAS28-ESR) <2.6. Drug persistence was calculated by Kaplan-Meier method. The comparison between treatment subgroups was performed by a chi-square test for remission data and by a log-rank test for drug survival. Moreover, DAS28-ESR remission rate has been corrected for drug discontinuation by using the LUNDEX formula (1) . Results: The overall study population included 591 patients (female 77.3%, mean age [± standard deviation, SD] 54.2±13.2 years, mean disease duration [±SD] 7.4±7.7 years, positive rheumatoid factor 67.5%, positive anti-citrullinated peptide antibodies 77.6%, mean baseline DAS28-ESR 5.1±1.2) treated with TCZ (n=61) or TNFis (n=530; infliximab 43, adalimumab 163, etanercept 195, golimumab 60, certolizumab pegol 69). Baseline characteristics were similar in the two groups, with the exception of mean age (TCZ 58.2 vs TNFis 53.7 years; p=0.021). No significant differences (p=0.361) emerged in the 6- (TCZ 88% vs TNFis 84.3%; p=0.752) and 12-month (TCZ 76.4% vs TNFis 71.5%;) retention rate. Clinical remission was achieved in overall 35.7% patients at 6 months (TCZ 59% vs TNFis 33%; p<0.001) and in 36.8% patients at 12 months (TCZ 58.8% vs TNFis 34.5%; p<0.001). Similar trends were observed after correction by LUNDEX formula at 6 (TCZ 51.9% vs TNFis 27.8%) and 12 months (TCZ 44.9% vs TNFis 24.6%). Conclusions: Despite a similar 1-year retention rate, the proportion of patients achieving DAS28-ESR remission was significantly higher in TCZ+MTX treated group compared with TNFis+MTX, suggesting a deeper clinical response in patients receiving IL6 blockade. References: Kristensen LE, et al. Arthritis Rheum 2006;54:600–6. Disclosure of Interest: None declared